Use of information and communication technologies to promote the learning process of students with intellectual disabilities - Vera-Mera, María Gema; Pinda-Román, Nathaly Jessenia; Loayza-Solórzano, Michelle Stefany; Ordoñez-Calva, Alexandra Fernanda; Olmedo-Zambrano, Verónica Ximena (International research journal of management, IT and social sciences, 2023)
Students with intellectual disabilities have difficulties in advancing in the teaching-learning process, because traditional methods are used by teachers, and this causes poor performance. The objective is to introduce the use of computer and communication technologies to improve academic capabilities, the methodology used was descriptive, qualitative, and bibliographic review. The results obtained indicate that the use of new technologies enhanced the abilities of the students, confirming cognitive improvements for learning the subjects, in this way it was proven that these tools allow greater development of the academic skills of each of them.